Performance Enhancement of Ce0.8Sm0.2O1.9-Supported SOFC by Electrophoretic Formation of Modifying BaCe0.8Sm0.2O3 and Ce0.8Sm0.1Pr0.1O1.9 Layers - Elena Pikalova; Elena Kalinina (Membranes, 2023)
The strategy to increase the performance of the single solid oxide fuel cell (SOFC) with a supporting membrane of Ce0.8Sm0.2O1.9 (SDC) electrolyte has been implemented in this study by introducing a thin anode barrier layer of the BaCe0.8Sm0.2O3 + 1 wt% CuO (BCS-CuO) electrolyte and, additionally, a modifying layer of a Ce0.8Sm0.1Pr0.1O1.9 (PSDC) electrolyte. The method of electrophoretic deposition (EPD) is used to form thin electrolyte layers on a dense supporting membrane. The electrical conductivity of the SDC substrate surface is achieved by the synthesis of a conductive polypyrrole sublayer. The kinetic parameters of the EPD process from the PSDC suspension are studied. The volt-ampere characteristics and power output of the obtained SOFC cells with the PSDC modifying layer on the cathode side and the BCS-CuO blocking layer on the anode side (BCS-CuO/SDC/PSDC) and with a BCS-CuO blocking layer on the anode side (BCS-CuO/SDC) and oxide electrodes have been studied. The effect of increasing the power output of the cell with the BCS-CuO/SDC/PSDC electrolyte membrane due to a decrease in the ohmic and polarization resistances of the cell is demonstrated. The approaches developed in this work can be applied to the development of SOFCs with both supporting and thin-film MIEC electrolyte membranes.